2020
DOI: 10.1002/jaal.1055
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Learning of Academic Vocabulary in Iceland

Abstract: Since 2000, there has been a steady decline in the reading comprehension performance on the Programme for International Student Assessment (PISA) (OECD, 2017) for Icelandic adolescents (Directorate of Education, 2017; Ólafsdóttir & Sigurðsson, 2017). No participating country has demonstrated a sharper drop in mean scores on this measurement. Icelandic educators are concerned that the large number of adolescents who demonstrate poor performance are not mastering advanced Icelandic vocabulary, as that is a key v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…It is believed that developing literacy skill should be started at early age. This idea was supported by experts that see the benefit of developing literacy skill as early as possible (Ólafsdóttir & Stefánsson, 2020;Taylor & Leung, 2020;Trainin & Vadasy, 2017). Teaching literacy in the early age should focus on concrete concept, meaningful, interesting, functional and engaging (Huh & Suh, 2017;Ratminingsih & Budasi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that developing literacy skill should be started at early age. This idea was supported by experts that see the benefit of developing literacy skill as early as possible (Ólafsdóttir & Stefánsson, 2020;Taylor & Leung, 2020;Trainin & Vadasy, 2017). Teaching literacy in the early age should focus on concrete concept, meaningful, interesting, functional and engaging (Huh & Suh, 2017;Ratminingsih & Budasi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in her study with Icelandic sixth and eighth graders, Ólafsdóttir (2015) found that proficient writers, who were able to organize their texts and present and give support for their arguments in a convincing way, used a higher number of Icelandic academic words compared to less proficient writers. However, while subject-specific words are normally taught explicitly within the corresponding discipline, teachers are often not cognizant of the importance of academic words that are used across a wider subject area (Beck et al, 2013;Ólafsdóttir et al, 2020;Roessingh 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Effective vocabulary instruction for all students is paramount as studies have shown that vocabulary knowledge is correlated with more enhanced reading comprehension (Beck, Perfetti, & McKeown, 1982;Blachowicz & Fisher, 2004;Cromley & Azevedo, 2007;Cunningham & Stanovich, 1997;Nagy & Scott, 2004;Olafsdottir, Laster, & Stefansoon, 2020;Stahl & Fairbanks, 1986). Additionally, students with larger vocabularies have shown increased stamina while reading (Stahl, 1999).…”
Section: Introduce the Problemmentioning
confidence: 99%